Perancangan Sistem Tracking Panel Surya Dual axis Menggunakan Sensor LDR dan RTC untuk Optimasi Penyerapan Energi Matahari - Irawan, Moh. Davit (Forum Pendidikan Tinggi Teknik Elektro Indonesia Pusat, 2025)
The continuously increasing demand for electrical energy presents significant challenges, particularly in Indonesia, which remains heavily dependent on coal-fired power plants (PLTU) as its primary energy source. This dependency raises sustainability concerns and environmental impacts. As a solution, the utilization of alternative energy sources, especially solar power, becomes a strategic approach. This study designs and implements a dual-axis tracking solar panel system based on an Arduino Mega 2560 microcontroller, equipped with Light Dependent Resistor (LDR) sensors for light intensity detection and a Real Time Clock (RTC) module for time synchronization. The tracking mechanism is programmed to continuously adjust the panel’s position, ensuring it remains perpendicular to the sun’s rays throughout the day. Performance testing was conducted by comparing the dual-axis tracking system with a static panel under identical environmental conditions. The results demonstrate an increase in electrical output by approximately 25–30% with the dual-axis tracking system compared to the static panel. Therefore, this system is proven to be effective in improving energy absorption efficiency and offers a promising solution for renewable energy utilization in Indonesia.